Degradasi Bahan Kering dan Produksi Asam Lemak Terbang In Vitro pada Kulit Buah Kakao Terfermentasi - Nelson, Nelson (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2011)
The research was conducted to investigate dry matter degradation and VFA production of fermented cocoa pods by Phanerochaete chrysosporium. The experiment method Completely Randomized Block Design with two factors: three treatment mineral supplementation and four treatment storage length. The result showed that  mineral  administration  had  no  effect  to  dry  matter  degradation, VFA  production,   ammonia concentration.  Fermentation  length  affected  volatile  fatty  acids  with  the  highest  production  at  day  10.  Mineral  supplementation  to  fermented  cacao  pods  had  no  optimal  yield  on  dry  matter  degradation,  VFA production, and ammonia production.